2021
DOI: 10.1186/s12917-021-02744-w
|View full text |Cite
|
Sign up to set email alerts
|

Change in the plasma proteome associated with canine cognitive dysfunction syndrome (CCDS) in Thailand

Abstract: Background Canine cognitive dysfunction syndrome (CCDS) is a progressive neurodegenerative disorder found in senior dogs. Due to the lack of biological markers, CCDS is commonly underdiagnosed. The aim of this study was to identify potential plasma biomarkers using proteomics techniques and to increase our understanding of the pathogenic mechanism of the disease. Plasma amyloid beta 42 (Aβ42) has been seen to be a controversial biomarker for CCDS. Proteomics analysis was performed for protein i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Although proteomic analysis of canine plasma is less performed than serum analysis, some studies on canine plasma have been reported, with the plasma proteins detected in dogs with SIRS and MODS being 68, 12 in obese dogs with and without obesity-related metabolic dysfunction, and nally 87 in dogs diagnosed with canine cognitive dysfunction syndrome respectively. (Kuleš et al, 2016;Tvarijonaviciute et al, 2016;Phochantachinda et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Although proteomic analysis of canine plasma is less performed than serum analysis, some studies on canine plasma have been reported, with the plasma proteins detected in dogs with SIRS and MODS being 68, 12 in obese dogs with and without obesity-related metabolic dysfunction, and nally 87 in dogs diagnosed with canine cognitive dysfunction syndrome respectively. (Kuleš et al, 2016;Tvarijonaviciute et al, 2016;Phochantachinda et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Routine blood tests in elderly dogs would show a mild increase of liver enzymes [31], with no other salient abnormalities being definitely confirmed to date. In canine patients with CDS, detection and quantification of soluble oligomers of β-amyloid fragments 1-40 and 1-42, hyperphosphorylated tau protein, and neurofilament light chain are considered promising, although not yet validated, blood biomarkers [31,32,[61][62][63][64][65].…”
Section: Putative Biomarkersmentioning
confidence: 99%
“…The pharmacological potential of um-PEA in controlling neuroinflammation-either singly or co-ultramicronized with the antioxidant luteolin (i.e., co-ultra PEA)-has been proven by numerous investigations in various models of neurodegenerative conditions and senile dementia, both in vitro and in vivo [241][242][243][244][245]. In rat hippocampal slices and neuroblastoma cells challenged with β-amyloid 1-42, PEA in the ultramicronized or coultramicronized formulation exhibited anti-inflammatory and anti-apoptotic effects, as well as the ability to decrease the expression of markers of oxidative stress and astroglial injuries, such as iNOS and GFAP [65,126]. In rats that received an intrahippocampal infusion of β-amyloid 1-42, chronic treatment for 14 days with co-ultra PEA prevented astrocyte hypertrophy as well as the production of pro-inflammatory cytokines and enzymes, compared to vehicle-treated animals [246].…”
Section: Dietary Supplementation With Pea-um As a Strategy To Control Age-related Neuroinflammation And Neurobehavioral Correlatesmentioning
confidence: 99%
“…The prevalence of CCDS is up to 60% in dogs, predominantly >11 years; however, the actual diagnosis rate remains quite low, at approximately 2% (5,12,14). Species-specific differences in CCDS have not been identified (12).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CCDS is up to 60% in dogs, predominantly >11 years; however, the actual diagnosis rate remains quite low, at approximately 2% (5,12,14). Species-specific differences in CCDS have not been identified (12). The major clinical signs of CCDS include apparent confusion, anxiety, disturbance of the sleep/wake cycle, and decreased interactions between pets and their owners (3).…”
Section: Introductionmentioning
confidence: 99%